A study on the annual change of cross-sectional data of physical strength and performance test among Junior high school elite divers selected annually from 1998 through 2005 - Goto, K.; Nomura, T.; Ogawa, M. (Japanese Journal of Sciences in Swimming and Water Exercise, 2007)
Physical strength and performance test (PSPT) results for elite junior divers selected annually in the diving competition finals of the National Junior High School Selection Swim Meets (1998~2005) were studied. It was found that the relationship between the PSPT results and the competition scores compared from the viewpoint of the annual results were as follows: the PSPT results for both genders indicated gradual improvements among male and female springboard divers, and male and female platform divers (ANOVA: p<0.05). The competition scores for springboard diving also indicated gradual improvements as mentioned above. Various athletic abilities, such as the flexibility of the shoulder joints, body tucks, etc., and especially muscular strength were improved during the PSPT. It was recognized that this unique improvement in the PSPT and competition scores have been achieved by using newly developed training systems.